2016
DOI: 10.1038/srep29637
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mediated impaired erythrocyte Lands’ Cycle is pathogenic for sickle cell disease

Abstract: Although Lands’ cycle was discovered in 1958, its function and cellular regulation in membrane homeostasis under physiological and pathological conditions remain largely unknown. Nonbiased high throughput metabolomic profiling revealed that Lands’ cycle was impaired leading to significantly elevated erythrocyte membrane lysophosphatidylcholine (LysoPC) content and circulating and erythrocyte arachidonic acid (AA) in mice with sickle cell disease (SCD), a prevalent hemolytic genetic disorder. Correcting imbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 64 publications
12
70
1
Order By: Relevance
“…54 Based on the consideration that, in order to transport and deliver oxygen, transfused RBCs must remain intact and circulate in the bloodstream of the recipient, correlative studies have been published in mice and humans suggesting a role for lipid and purine oxidation (e.g., 5-hydroxyeisosatetraenoic acid and other hydroxyeisosatetraenoic acids, ATP, and hypoxanthine) in mediating RBC hemolysis and posttransfusion recovery. 24,35,55,56 These observations are relevant in that In the present study, we generated metabolomics data on five storage additives, including SAGM, the canonical European storage solution, and more recently introduced PAGGSM, as well as three alkaline additives (SOLX, E-SOL 5, and PAG3M). Of note, results on SAGM and PAGGSM we report here are consistent with findings reported by Rolfsson and colleagues, 39 who also explored the metabolic impact of other nonalkaline additives such as AS-1 and AS-3, but did not focus on the impact of intracellular alkalinization on stored erythrocyte metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…54 Based on the consideration that, in order to transport and deliver oxygen, transfused RBCs must remain intact and circulate in the bloodstream of the recipient, correlative studies have been published in mice and humans suggesting a role for lipid and purine oxidation (e.g., 5-hydroxyeisosatetraenoic acid and other hydroxyeisosatetraenoic acids, ATP, and hypoxanthine) in mediating RBC hemolysis and posttransfusion recovery. 24,35,55,56 These observations are relevant in that In the present study, we generated metabolomics data on five storage additives, including SAGM, the canonical European storage solution, and more recently introduced PAGGSM, as well as three alkaline additives (SOLX, E-SOL 5, and PAG3M). Of note, results on SAGM and PAGGSM we report here are consistent with findings reported by Rolfsson and colleagues, 39 who also explored the metabolic impact of other nonalkaline additives such as AS-1 and AS-3, but did not focus on the impact of intracellular alkalinization on stored erythrocyte metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several metabolites identified in the screen include nucleosides (eg, adenosine), lipids (eg, sphingosine-1-phosphate [S1P], lysophospholipids, and free acyl fatty acids), and glycolytic intermediates (eg, 2,3bisphosphoglycerate [2,3-BPG]), which are significantly elevated in SCD blood. [23][24][25] In contrast, glutathione levels are significantly reduced. 26 Thus, metabolomics profiling reveals overall specific metabolic changes in SCD mice.…”
Section: Metabolomics Identifies Overall Metabolite Changes In Scd Micementioning
confidence: 98%
“…Metabolomics revealed that erythrocyte membrane lysophosphatidylcholine and circulating erythrocyte-derived arachidonic acid levels are elevated in SCD erythrocytes, which suggests that the Lands' cycle is impaired. 24 In vivo mouse studies showed that elevated PLA2 contributes to sickling, inflammation, and multiple tissue damage in SCD mice. 24 Cultured human sickle erythrocytes were treated with PLA2 small interfering RNAs, which reduced PLA2 activity and decreased sickling.…”
Section: Impaired Lands' Cycle Underlies Sickling In Humans and Mice mentioning
confidence: 99%
“…Sickle-cell mice and control mice were generated by BMT as previously described (16)(17)(18). Prior to irradiation, recipient mice were treated with 0.2% neomycin for at least 48 h and were continuously treated for 2 wk postirradiation.…”
Section: Bmtmentioning
confidence: 99%
“…As previously described (17,18), BMT was performed to generate SCD → Per2 Luc mice and control mice. Sickle transplant mice expressing chimerism above 85% were used for experiments.…”
Section: Bioluminescence Recordings For Detecting Per2 Expression In mentioning
confidence: 99%